ANALYZING OF NEAREST NEIGHBORHOOD CHARACTERISTICS OF TROPICAL BROADLEAVED FOREST STANDS - Hong Hai, Nguyen (Journal of Forestry Science and Technology, 2017)
Spatial structure is one of the major parameters for describing forest stand structure. We applied a new method to quantitative analysis spatial structure of forest stand based on nearest neighbour distance between tree groups. Three 1-ha plots (100 m x 100 m) were designed on the tropical broadleaved forests to validate the distribution of structural parameters. All tree with diameter at breast high (DBH) ≥ 6 cm were mapped, measured tree DBH and classified species. We calculated and described structural parameters such as Mingling, DBH dominance and Uniform Angle Index by using Crancod and Microsoft Excel softwares. The results showed that: most of studied species were found highly mixed with other species. In DBH dominance analysis, most of dominant tree species in Ha Tinh and Binh Dinh plots were less competition in tree DBH comparing to nearest neighbours. However, three species had positive advantage in tree size, therefore bearing higher competitive capacity for nutrient resources. About spatial distribution, most of tree species in three studied plots were from regular to clumped patterns but mainly focused at random pattern. The spatial structural parameters offer direct information and valuable about spatial structure of forest stand. Those information can be used in thinning of sustainable forest management, modelling and restoration.